2015
DOI: 10.1108/jmtm-05-2012-0053
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory survey of green supply chain management in Chinese manufacturing small and medium-sized enterprises

Abstract: Purpose – The purpose of this paper is to empirically investigate the pressures and drivers that have been experienced by Chinese manufacturing small and medium enterprises (SMEs) in terms of green supply chain management (GSCM). Design/methodology/approach – The research framework and hypotheses are examined by a questionnaire survey through e-mails conducted in China in 2011. The empirical analysis is based on the data from 202 SME man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 62 publications
(101 reference statements)
3
64
0
1
Order By: Relevance
“…Hitchcock [157] carried out a theoretical study highlighting difficulties that arise in logistics services industry (e.g., UK and China) concerning environmental sustainability adoption. Huang et al [158] carry out a survey to investigate pressures impacting on LSP selection of small and medium-sized companies in China. Seuring [159] provides empirical methods highlighting intuitions resulting from some projects contributing to obtain a better understanding of green supply chain management.…”
Section: Ta4 Customer Perspective In Energy-efficient and Sustainablmentioning
confidence: 99%
“…Hitchcock [157] carried out a theoretical study highlighting difficulties that arise in logistics services industry (e.g., UK and China) concerning environmental sustainability adoption. Huang et al [158] carry out a survey to investigate pressures impacting on LSP selection of small and medium-sized companies in China. Seuring [159] provides empirical methods highlighting intuitions resulting from some projects contributing to obtain a better understanding of green supply chain management.…”
Section: Ta4 Customer Perspective In Energy-efficient and Sustainablmentioning
confidence: 99%
“…In addition, this can help improve customer satisfaction, because of having close contact with customers and local organisations, SMEs have greater opportunities in understanding, encouraging and collaborating with customers for environmental practices. The GSCM practices proposed by were implemented in Chinese SMEs by (Huang et al, 2012;Huang et al, 2015). These practices have won some recognition and were adopted by some later studies including Lee et al(2012), and Laosirihongthong et al (2013).…”
Section: Morrisonmentioning
confidence: 99%
“…Tseng et al (2015) claimed that GSCM practices and firm performance have been comprehensibly studied but firms are unlikely to perform well without depending on the resources of partners in their supply chains. For SMEs due to the scarcity of resources including technological know-hows, knowledge and expertise, human and financial resources (Lee et al, 2012;Huang et al, 2015), dependence on the partners in their supply chains become critical. In order to minimise risks and complexities in their supply chains, inter-firm dependence to improve firm performance become inevitable.…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important for academicians to identify the determinants that would influence the adoption of environmental innovations by SMEs in Malaysia. This research is vital since limited studies are found that focused on environmental behavior of SMEs in developing countries. Previous literatures showed that various types of determinants have been tested to see their influence on adoption of various environmental innovations [10][11][12][13][14][15][16][17]. The determinants however, can be classified into three main factors which are technological factor, organizational factor and environmental factor.…”
Section: Introductionmentioning
confidence: 99%